Service Management and Patient Satisfaction in Independent Midwifery Clinical Practice - Anjani, Arum Dwi; Aulia, Devy Lestari Nurul; Wulandari, Nayala; Susanti, Alya; Oktaviona, Niza; Berlianti, Jihan Fia (Newinera Publisher, 2025)
Midwifery services in independent clinical practices play a crucial role in the primary healthcare system, particularly in providing care for mothers and children. This study aims to analyze the relationship between service management and patient satisfaction levels in independent midwifery clinical practices (PMB). A descriptive qualitative approach was employed, using the PRISMA method to trace and analyze data from various scholarly sources related to service management and patient satisfaction in PMBs. Key dimensions from the SERVQUAL model reliability, responsiveness, empathy, assurance, and tangible aspects served as the main indicators for assessing service quality. Case studies from several PMBs demonstrate that the use of simple technologies, effective communication, and efficient time management contribute significantly to high levels of patient satisfaction. Conversely, unstructured management practices negatively affect perceptions of care. The findings underscore the importance of enhancing midwives’ managerial capacity, developing standard operating procedures (SOPs), and conducting routine evaluations of patient experiences to maintain service quality. These results offer strategic insights into strengthening PMBs as a responsive and high-quality pillar of maternal healthcare services.